Tsallis Holographic Dark Energy with Granda-Oliveros Scale in (n+1)-Dimensional FRW Universe - Ayman A. Aly (Advances in Astronomy)
Based on Tsallis holographic dark energy model recently proposed by using the general model of the Tsallis entropy expression, we reconstruct cosmographic parameters, q,j,κ,l, and we study their evolution in spatially flat (n+1)-dimensional Friedmann-Robertson-Walker universe using Granda-Oliveros scale. Our results show that the universe is in an accelerating expansion mode described by phantom-like behavior. We go further and study the state finder operators and the Om diagnostic to understand the behavior of our model. The stability of the system is also studied by using the square of speed of sound showing that our model is stable over the low range of red-shift considered. The results indicate that the entropy formalism will play an important role in understanding the dynamics of our universe.